IMPLEMENTASI GOOD CORPORATE GOVERNANCE DALAM UPAYA MENINGKATKAN KINERJA PERUSAHAAN - Putri, Erika Priscilla; Pradana, Bayu Ilham (Jurnal Management Risiko dan Keuangan, 2022)
The objective of this research is to identify the implementation of good corporate governance at PT. ASABRI (Persero) branch office of Surabaya in the effort of enhancing their performance. Here the company serves as the research object. The data was harvested through interviews, observations, and documentations and was analyzed using Miles-Huberman interactive analysis. This study finds that, in order to improve their performance, the company has well implemented good corporate governance principles consisting of accountability, responsibility, independency, and fairness. However, transparency has not been optimal since the branch office is merely a user; the manager is the head office. The well implementation of good corporate governance can increase the company’s performance and their image for the people.